2022
DOI: 10.3390/antiox11122430
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Blunted Nocturnal Decrease in Diastolic Blood Pressure and Oxidative Stress: An Observational Study

Abstract: An impaired nocturnal decrease in diastolic blood pressure (DBP) increases the blood pressure (BP) load, which is a main factor in endothelial dysfunction, atherosclerosis, and arterial stiffness. We aimed to quantify some markers of oxidative stress in hypertensive patients, to compare their levels between individuals with dipper and non-dipper DBP profiles, and to assess their correlation with the nocturnal DBP (nDBP) dipping. It was an observational study that included patients older than 18 years with a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In this sense, elevated levels of Lp(a) have been established as a critical pro-oxidant and pro-inflammatory insult within the vascular wall, promoting endothelial dysfunction. Consequently, these heightened Lp(a) levels may be also linked to specific nocturnal BP abnormalities [40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, elevated levels of Lp(a) have been established as a critical pro-oxidant and pro-inflammatory insult within the vascular wall, promoting endothelial dysfunction. Consequently, these heightened Lp(a) levels may be also linked to specific nocturnal BP abnormalities [40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, multiple studies have suggested that improved redox status contributes to maintaining adequate BP control. Oxidative stress and endothelial dysfunction are essential conditions for developing vascular tone abnormalities that influence BP levels and the circadian rhythm of BP [ 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, hypertensive patients with bedtime use of RAAS blockers showed a joint variation of nDBP decrease with reduced thiol levels that we did not find in patients with morning-time use. Some studies in AHT, circadian BP profile, and redox markers support a relationship between the levels of protein oxidation markers and BP figures, while reduced thiol concentrations have also been correlated with the nDBP decrease [ 19 , 29 ]. However, the influence of chronotherapy on the interrelationship between protein oxidation markers and BP indices remains unknown.…”
Section: Discussionmentioning
confidence: 99%